La protección de la persona prostituta en la sentencia T-269 de 2010 (2014)
The following image needs no explanation. It represents the attitude assumed when facing a lot of social problems: it is better to hide its causes than intervene them. It is easier to postpone the solution (in case a problem is considered to exist) than to implement it. It just so happened in the 30’s with alcohol, abortion, gambling, drug use, and prostitution. Any attitude assumed towards them –forbiddance, abolition, regulative- depends, with no doubt, of the knowledge held on social reality. There are a number of examples that show the precarious relation weaved between Sociology and Law, when giving solution to certain problems through the issuing of legal norms, be them laws or sentences. One of the challenges for Lawyers is to recognize and never forget somethins so basic: Law is a cultural object, and as such, all process of norm creation, interpretation, and application should be accompanied by the study of social circumstances.